Measuring university students attitudes toward revenge - Fadiel Hassan, Haider (Al-Adab Journal, 2020)
Revenge is an issue that occurs between individuals, caused by the difficulty of tolerating in some individuals with the abuses they encounter in all their stripes. Retaliation: It is the intention to see the aggressor suffer. This research aims to build a measure of university students ’attitudes toward revenge and measure these trends, and to identify the differences in university students’ attitudes toward revenge on the gender variable and the variable of academic specialization. The research sample consisted of (100) male and female students from the human and scientific specializations. The researcher built a measure of university students’ attitudes toward revenge, which consists of (20) paragraphs, and was applied to the research sample. The results of the research showed that university students have negative attitudes towards revenge, and that there are statistically significant differences in the attitudes of university students towards revenge according to the gender variable and in favor of males, and the results also showed that there are no statistically significant differences in the attitudes of university students towards revenge according to the academic specialization, In the light of its results, the research reached a set of recommendations and proposals.